Drag characteristics of competitive swimming children and adults - Kjendlie, P. L.; Stallman, R. K. (Journal of Applied Biomechanics, 2008)
The aims of this study were to compare drag in swimming children and adults, quantify technique using the technique drag index (TDI), and use the Froude number (Fr) to study whether children or adults reach hull speed at maximal velocity (vmax). Active and passive drag was measured by the perturbation method and a velocity decay method, respectively, including 9 children aged 11.7 ± 0.8 and 13 adults aged 21.4 ± 3.7. The children had significantly lower active (kAD) and passive drag factor (kPD) compared with the adults. TDI (kAD/kPD) could not detect any differences in swimming technique between the two groups, owing to the adults swimming maximally at a higher Fr, increasing the wave drag component, and masking the effect of better technique. The children were found not to reach hull speed at vmax, and their Fr were 0.37 ± 0.01 vs. the adults 0.42 ± 0.01, indicating adults` larger wave-making component of resistance at vmax compared with children. Fr is proposed as an evaluation tool for competitive swimmers.